1962
DOI: 10.1002/j.2050-0416.1962.tb06341.x
|View full text |Cite
|
Sign up to set email alerts
|

Hop Oil I. Preliminary Investigations of the Oxygenated Fraction

Abstract: Gas chromatography of the oxygenated constituents of hop oil indicated the presence of a number of high boiling point non‐saponifiable compounds in addition to the previously recognized constituents. Methyl geranate appears to be the principal ester present in the oil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1964
1964
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…It has been proposed that geranic acid is a derivative of geraniol and geranial, which are known as hop-derived flavor compounds, especially present in flavor hops. ,− ,, In previous studies, geranic acid was found in lemongrass, ginger, lemon oil, tomato, and grape, which are raw materials used for wine making. Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. ,,, Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, which they first identified in hop oil . Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proposed that geranic acid is a derivative of geraniol and geranial, which are known as hop-derived flavor compounds, especially present in flavor hops. ,− ,, In previous studies, geranic acid was found in lemongrass, ginger, lemon oil, tomato, and grape, which are raw materials used for wine making. Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. ,,, Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, which they first identified in hop oil . Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L) .…”
Section: Resultsmentioning
confidence: 99%
“…Methyl geranate, which is a methyl ester of geranic acid, has been reported as a compound derived from hop oil. 19,20,35,36 Roberts et al assumed geranic acid to be a possible precursor of methyl geranate, 36 which they first identified in hop oil. 35 Peacock et al analyzed three commercial beers and detected geranic acid in only one of the beer samples at trace levels (1 μg/L).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition and influence of the essential oil of hops in brewing have been the subjects of a number of earlier reviews (61,182,193,325). a. introduction Hops contain 0.5-1.5% of essential oil which can be separated by distillation in steam and recovered from the distillate either by solvent extraction or by the use of an oil trap which allows the aqueous phase to return to the boiler (54,190,321,365,422). In the first method the oil will contain water-soluble aliphatic acids which are washed out in an oil trap.…”
Section: Essential Oil Constituentsmentioning
confidence: 99%
“…The components resolved by gas chromatography have been identified by retention data and, after recovery in a suitable trap, by physical techniques such as infrared and proton magnetic resonance spectroscopy and/or mass spectrometry. The advances in gas chromatographic technique over the past decade have led to the recognition of an increasing number of trace constituents in hop oil (146,147,221,222,321,323). The most refined technique used to date consists of gas chromatography using a high-resolution capillary column coupled directly to a time-of-flight mass spectrometer (74, [77][78][79].…”
Section: Essential Oil Constituentsmentioning
confidence: 99%